PENGARUH MOTIVASI KERJA TERHADAP KINERJA PEMANDU LALU LINTAS UDARA DALAM RANGKA MENINGKATKAN PELAYANAN KESELAMATAN PENERBANGAN DI PERUM LPPNPI KANTOR CABANG PEMBANTU LAMPUNG - Doni Saputra; Kusno; Besar Ajisanto (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Work motivation can spur employees to work better so that they can achieve the main goals of the company organization. As well as to improve the quality of performance, management must strive to increase work motivation. Employees who have high work motivation, always have the enthusiasm or drive to work hard. As energy to generate impulses in yourself so as to achieve a goal. Motivating the workforce of Air Traffic Controllers is the answer to the problems faced by the company. The problem that is reviewed in this final project is the extent to which the influence of work motivation on improving the performance of air traffic controllers at Perum LPPNPI Lampung Sub-Branch Office. Especially for air traffic controllers, giving motivation is expected to be able to foster morale in the midst of work pressures at hand. This study aims to obtain an overview of whether there is an influence between motivation on the performance of air traffic controllers. In addition, the benefits for researchers are that it can increase knowledge in the field of air traffic guidance, in particular about the work motivation of air traffic guidance services, which is related to air traffic control. efforts to improve air traffic safety. The method used is a data analysis method using a qualitative approach. Qualitative research is carried out under natural conditions and is discovery in nature. This study emphasizes more on meaning and is value bound. Qualitative research is used when problems are not clear, to find hidden meanings, to understand social interactions, to develop theories, to ascertain the correctness of data, and to examine historical developments.